Connecting Purchases With Customer Valueusing CRM Methods - Dea Agatha Sesariza (AIBPM Publisher, 2018)
This paper aims to examine various concepts associated with the development of definitions and dimensions of customer relationship management, and strive to develop a comprehensive model of customer relationship management. Customer Relationship Management (CRM) is one of the ways to maintain continuous relationship between a company and its stakeholders as well as its shareholder. A lot of companies are using CRM to maintain its relationship with the customers. By using CRM, the companies will be able to find out their customers’ needs and wants so that emotionally they an be involved with each other. This enables them to have a two-way communication. As a result, they will have close and open business relationship which makes the customers, especially, loyal to the companies; and they will not easily change their preference to another product or brand. Customer relationshipmanagement (CRM) raises misconceptions, such as: technology, marketing, and loyalty. Key Word: Customer relationshipmanagement, stakeholders, technology, marketing, and loyalty